Cold-rolled strip steel anti-rust oil containing TiO2 nanoparticles and preparation method of cold-rolled strip steel anti-rust oil

By adding TiO2 nanoparticles and other ingredients to the anti-rust oil of cold-rolled strip steel, a uniformly dispersed anti-rust film is formed, which solves the problem of corrosion of cold-rolled strip steel, significantly improves the anti-rust performance and service life, and meets environmental protection. and safety requirements.

CN119144370AActive Publication Date: 2024-12-17ANGANG STEEL CO LTD

Patent Information

Application Number
CN202411210867.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-30
Publication Date
2024-12-17
Estimated Expiration
2044-08-30

AI Technical Summary

Technical Problem

Cold-rolled strip steel is susceptible to corrosion and rust during processing, transportation and use. The anti-rust effect and use performance of traditional anti-rust oil are limited, and the environmental protection and safety requirements are not high.

Method used

Develop a cold-rolled strip steel anti-rust oil containing TiO2 nanoparticles. By reasonably selecting and proportioning components, including TiO2 nanoparticles, composite surface modification agent, composite base oil, composite anti-rust agent, composite extreme pressure anti-wear agent , composite oily agent, composite antioxidant and composite defoaming agent, surface modification and stirring reaction process are used to form a uniformly dispersed anti-rust film to improve anti-rust performance.

Benefits of technology

It significantly improves the weather resistance and protection performance of anti-rust oil, extends the service life of metal surfaces, and meets environmental protection and safety needs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005020285670000051
    Figure BDA0005020285670000051
  • Figure BDA0005020285670000071
    Figure BDA0005020285670000071
Patent Text Reader

Abstract

The invention discloses cold-rolled strip steel anti-rust oil containing TiO2 nanoparticles and a preparation method of the cold-rolled strip steel anti-rust oil. The cold-rolled strip steel anti-rust oil comprises the following components: TiO2 nanoparticles, a composite surface modifier, composite base oil, a composite anti-rust agent, a composite extreme pressure anti-wear agent, a composite oiliness agent, a composite antioxidant and a composite defoaming agent. According to the method, the nanotechnology and the anti-rust technology are combined, the anti-rust oil with excellent anti-rust performance is developed, the adhesion of an oil film is enhanced through nanoscale TiO2 particles, the anti-rust performance of the anti-rust oil is effectively improved, and the storage life and the service life of cold-rolled strip steel are prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of metal rust prevention and particularly relates to a method for preparing a metal rust-proofing agent containing TiO 2 Nanoparticle antirust oil for cold-rolled strip steel and preparation method thereof. Background Art

[0002] As an important metal material, cold-rolled strip steel has been widely used in the fields of automobiles, home appliances, and construction. However, cold-rolled strip steel is susceptible to corrosion and rust during processing, transportation, and use, which not only affects its appearance and performance, but may also cause safety hazards. Anti-rust oil is a commonly used anti-rust material for metal surfaces. It can form a protective film to isolate the metal surface from contact with corrosive media such as air and water to achieve the purpose of rust prevention. Traditional anti-rust oil mainly uses petroleum base oil and a single anti-rust additive, and the anti-rust effect and performance are limited. However, with the continuous advancement of science and technology, anti-rust oil has gradually developed in the direction of high efficiency, environmental protection, and multi-function; among them, the application of nanotechnology has become an important milestone in the development of anti-rust oil. Titanium dioxide nanoparticles are a new type of nanomaterial. Adding titanium dioxide nanoparticles to anti-rust oil can significantly improve the weather resistance and protective performance of anti-rust oil, and play a better protective role on the metal surface. By continuously optimizing the preparation method and formula ratio of titanium dioxide nanoparticles, the anti-rust performance of anti-rust oil can be improved to meet the needs of different uses. At the same time, as people pay more and more attention to environmental protection and safety, anti-rust oil containing titanium dioxide nanoparticles, as an environmentally friendly and safe metal anti-rust material, will be more widely used and promoted in future development. Summary of the invention

[0003] The present invention combines nanotechnology with anti-rust technology, and develops anti-rust oil with excellent anti-rust performance and stability by reasonably selecting and proportioning various components, thereby improving the protective effect and service life of the metal surface.

[0004] In order to achieve the above-mentioned object of the invention, the present invention provides a TiO 2 Nanoparticle cold-rolled steel strip antirust oil, the cold-rolled steel strip antirust oil comprises the following components in parts by weight: TiO 2 3-10 parts of nanoparticles, 2-10 parts of composite surface modifiers, 70-90 parts of composite base oils, 5-15 parts of composite rust inhibitors, 0.5-3 parts of composite extreme pressure antiwear agents, 1-5 parts of composite oiliness agents, 1-5 parts of composite antioxidants, and 0.5-3 parts of composite defoaming agents.

[0005] In the above technical solution, further, the TiO 2The particle size of nanoparticles is in the range of 30 to 50 nm. Smaller particle size is conducive to the uniform dispersion and stable existence of nano-titanium dioxide in anti-rust oil, thereby improving the anti-rust effect. At the same time, smaller particle size also means a larger specific surface area, which can increase the contact area with the metal surface and form a denser anti-rust film. As one of the core rust inhibitors, adding titanium dioxide nanoparticles to anti-rust oil can significantly improve the weather resistance and protective performance of the anti-rust oil, and play a better protective role on the metal surface.

[0006] Furthermore, the composite surface modifier is prepared by mixing a silane coupling agent, stearic acid and octadecenoic acid in a weight ratio of (2-3):2:1. The composite surface modifier is used to improve the dispersibility and stability of titanium dioxide nanoparticles in base oil, so that the nanoparticles are evenly dispersed in the oil.

[0007] Furthermore, the composite base oil is prepared by mixing poly-alpha-olefin (PAO), dioctyl sebacate and triethyl phosphate in a weight ratio of (7-8):2:1, and the composite base oil serves as a main oily medium to achieve lubrication and rust prevention effects.

[0008] Furthermore, the composite rust inhibitor is prepared by mixing barium petroleum sulfonate, aluminum stearate and zinc naphthenate in a weight ratio of (4-5):3:2.

[0009] The composite extreme pressure anti-wear agent is prepared by mixing sulfur chloride, sulfurized fatty acid ester and tricresyl phosphate in a weight ratio of 2: (2-3): 1.

[0010] The composite oiliness agent is prepared by mixing stearic acid, butyl stearate and chlorinated paraffin in a weight ratio of 2: (2-3): 1.

[0011] The composite antioxidant is prepared by mixing 2,6-di-tert-butyl-4-methylphenol (BHT) and didodecanol thiodipropionate (DLTDP) in a weight ratio of (1-2):1.

[0012] The composite defoamer is prepared by mixing methyl silicone oil and a polyether defoamer (L62) in a weight ratio of 1:(1-2).

[0013] A kind of above-mentioned containing TiO 2 A method for preparing nanoparticle cold-rolled strip steel antirust oil, the preparation method comprising the following steps:

[0014] ① Surface modification of TiO 2 Nanoparticles: TiO 2The nanoparticles are mixed with the prepared composite surface modifier, stirred at 800-1000 rpm for 120-150 minutes at 80-95°C to ensure that the nanoparticles and the modifier are fully contacted and reacted. Then, a filter (with a filtration accuracy of 1-5 μm) is used to filter to remove unreacted modifiers and impurities, and the surface-modified TiO is obtained by drying at 90-120°C to constant weight. 2 Nanoparticles.

[0015] ② Preheating of composite base oil: Place the composite base oil (mixture of polyα-olefin and dioctyl sebacate or triethyl phosphate) in a selected ratio in a heating container, turn on the heating device, and gradually raise the temperature of the composite base oil to 70℃~85℃. This temperature range helps to ensure uniform dispersion of additives in the oil and reduce oil quality deterioration caused by excessive temperature. Maintain the stirring speed at 800~1000 rpm, add the surface-modified TiO obtained in step ① 2 The nanoparticles were stirred for 30 to 45 minutes.

[0016] ③ Add the composite rust inhibitor: Add a mixture of barium petroleum sulfonate, aluminum stearate and zinc naphthenate, which can effectively protect the metal surface from corrosion. Add slowly and evenly to avoid excessive local concentration, and keep the stirring speed at 900-1100 rpm and the stirring time for 15-20 minutes.

[0017] ④ Add the composite extreme pressure anti-wear agent: add a mixture of sulfur chloride, sulfurized fatty acid ester and tricresyl phosphate, which can significantly improve the extreme pressure and anti-wear properties of the rust-proof oil, and maintain the stirring speed at 1300-1500 rpm for 15-20 minutes.

[0018] ⑤ Add the composite oiliness agent: add a mixture of stearic acid, butyl stearate and chlorinated paraffin, and maintain a stirring speed of 1500-1700 rpm for 15-25 minutes. The oiliness agent can enhance the lubrication and adhesion properties of the rust-proof oil.

[0019] ⑥ Adding the composite antioxidant: adding a mixture of 2,6-di-tert-butyl-4-methylphenol (BHT) and didodecanol thiodipropionate (DLTDP), and maintaining a stirring speed of 1600 to 1800 rpm for 20 to 30 minutes. The antioxidant can effectively extend the service life of the anti-rust oil and prevent the oil from oxidative deterioration.

[0020] ⑦ Add the composite defoamer: Finally, add a mixture of methyl silicone oil and polyether defoamer (L62), and maintain a stirring speed of 1800 to 2000 rpm for 30 to 45 minutes. The defoamer can eliminate the foam generated by the rust-proof oil during use and improve the use effect.

[0021] ⑧ After all the above components are added, continue to stir at a speed of 1800-2000 rpm for 120-150 minutes until the temperature of the anti-rust oil drops to room temperature. 2 Nanoparticle anti-rust oil for cold rolled steel strip.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] The present invention combines nanotechnology with anti-rust technology, and develops an anti-rust oil with excellent anti-rust performance and stability by rationally selecting and proportioning the components. 2 The particles enhance the adhesion and uniformity of the oil film, effectively improve the anti-rust performance, and extend the storage and service life of the cold-rolled strip. DETAILED DESCRIPTION

[0024] The present invention is further described below in conjunction with specific examples, but the present invention is not limited in any way. To avoid redundant description, the raw materials in the following examples are all commercially available products unless otherwise specified, and the methods used are all conventional methods unless otherwise specified.

[0025] A TiO 2 Nanoparticle cold-rolled steel strip antirust oil, the cold-rolled steel strip antirust oil comprises the following components in parts by weight: TiO 2 3-10 parts of nanoparticles, 2-10 parts of composite surface modifiers, 70-90 parts of composite base oils, 5-15 parts of composite rust inhibitors, 0.5-3 parts of composite extreme pressure antiwear agents, 1-5 parts of composite oiliness agents, 1-5 parts of composite antioxidants, and 0.5-3 parts of composite defoaming agents.

[0026] A kind of above-mentioned containing TiO 2 A method for preparing nanoparticle cold-rolled strip steel antirust oil, the preparation method comprising the following steps:

[0027] ① Surface modification of TiO 2 Nanoparticles: TiO 2 The nanoparticles are mixed with the prepared composite surface modifier, and stirred at a temperature of 80°C to 95°C and a speed of 800 to 1000 rpm for 120 to 150 minutes; the surface-modified TiO 2 The nanoparticles were filtered and then dried at 90℃~120℃ to constant weight to obtain surface-modified TiO 2 Nanoparticles;

[0028] ② Preheating the composite base oil: Heat the composite base oil to 70℃~85℃, stir at 800~1000 rpm, add the surface-modified TiO obtained in step ① 2Nanoparticles, stirring for 30-45 minutes;

[0029] ③ Add the composite rust inhibitor, stir at a speed of 900 to 1100 rpm, and stir for 15 to 20 minutes;

[0030] ④ Add the composite extreme pressure anti-wear agent, stir at a speed of 1300-1500 rpm, and stir for 15-20 minutes;

[0031] ⑤ Add the composite oiliness agent, stir at a speed of 1500-1700 rpm, and stir for 15-25 minutes;

[0032] ⑥ Add the composite antioxidant, stirring at a speed of 1600-1800 rpm, and stir for 20-30 minutes;

[0033] ⑦ Add the composite defoamer, stir at a speed of 1800-2000 rpm, and stir for 30-45 minutes;

[0034] ⑧ After all the above components are added, stir at a stirring speed of 1800-2000 rpm for 120-150 minutes until the temperature of the rust-proof oil drops to room temperature to obtain a TiO 2 Nanoparticle anti-rust oil for cold rolled steel strip.

[0035] The matters not described in the following embodiments are the same as the description of the above specific implementation methods.

[0036] Example

[0037] A TiO 2 The components and mass contents of the nanoparticle antirust oil for cold-rolled steel strips of Examples 1-10 are shown in Table 1.

[0038] Table 1 Examples 1-10 contain TiO 2 Composition and content of nanoparticle antirust oil for cold-rolled steel strip

[0039]

[0040] A kind of above-mentioned containing TiO 2 A method for preparing nanoparticle cold-rolled strip steel antirust oil, the preparation method comprising the following steps:

[0041] ① Surface modification of TiO 2 Nanoparticles: TiO 2Nanoparticles (particle size 30nm) were mixed with the prepared composite surface modifier, stirred at 95°C and 1000 rpm for 150 minutes to ensure that the nanoparticles and the modifier were fully contacted and reacted. Then, a filter (filtration accuracy of 5μm) was used to filter to remove unreacted modifiers and impurities, and dried at 120°C to constant weight to obtain the surface-modified TiO 2 Nanoparticles.

[0042] The composite surface modifier is prepared by mixing a silane coupling agent, stearic acid and octadecenoic acid in a weight ratio of 3:2:1, and stirring at a speed of 400 rpm for 20 minutes.

[0043] ② Preheating of composite base oil: Place the composite base oil (a mixture of poly-α-olefin and dioctyl sebacate or triethyl phosphate) in a selected ratio in a heating container, turn on the heating device, and gradually raise the temperature of the composite base oil to 85°C. This temperature range helps to ensure uniform dispersion of additives in the oil and reduce oil quality degradation caused by excessive temperature. Keep the stirring speed at 1000 rpm and add the surface-modified TiO 2 The nanoparticles were stirred for a further 45 minutes.

[0044] The composite base oil is prepared by mixing polyalphaolefin PAO, dioctyl sebacate and triethyl phosphate in a weight ratio of 8:2:1, and stirring at a speed of 500 rpm for 10 minutes.

[0045] ③ Add the composite rust inhibitor: add a mixture of barium petroleum sulfonate, aluminum stearate and zinc naphthenate in a weight ratio of 5:3:2. These rust inhibitors can effectively protect the metal surface from corrosion. Add slowly and evenly to avoid excessive local concentration, and keep the stirring speed at 1100 rpm for 20 minutes.

[0046] ④ Add the composite extreme pressure anti-wear agent: the extreme pressure anti-wear agent can significantly improve the extreme pressure performance and anti-wear performance of the anti-rust oil, and maintain the stirring speed at 1500 rpm for 20 minutes.

[0047] The composite extreme pressure anti-wear agent is prepared by mixing sulfur chloride, sulfurized fatty acid ester and tricresyl phosphate in a weight ratio of 2:3:1, and stirring at a speed of 400 rpm for 15 minutes.

[0048] ⑤ Add the composite oiliness agent: and maintain the stirring speed at 1700 rpm for 25 minutes. The oiliness agent can enhance the lubrication and adhesion properties of the rust-proof oil.

[0049] The composite oiliness agent is prepared by mixing stearic acid, butyl stearate and chlorinated paraffin in a weight ratio of 2:3:1, and stirring at a speed of 600 rpm for 25 minutes.

[0050] ⑥ Adding the composite antioxidant: adding a mixture of 2,6-di-tert-butyl-4-methylphenol and didodecanol thiodipropionate, and maintaining a stirring speed of 1600 to 1800 rpm for 30 minutes. The antioxidant can effectively extend the service life of the anti-rust oil and prevent the oil from oxidative deterioration.

[0051] The composite antioxidant is prepared by mixing 2,6-di-tert-butyl-4-methylphenol (BHT) and didodecanol thiodipropionate (DLTDP) in a weight ratio of 2:1, and stirring at a speed of 400 rpm for 20 minutes.

[0052] ⑦ Add the composite defoamer: Finally, add the mixture of silicone oil and polyether defoamer, and keep the stirring speed at 2000 rpm for 45 minutes. The defoamer can eliminate the foam generated by the anti-rust oil during use and improve the use effect.

[0053] The composite defoamer is prepared by mixing methyl silicone oil and polyether defoamer (L62) in a weight ratio of 1:2, and stirring at a speed of 300 rpm for 10 minutes.

[0054] ⑧ After all the above components are added, continue to stir at a speed of 2000 rpm for 150 minutes until the temperature of the anti-rust oil drops to room temperature, and a TiO 2 Nanoparticle anti-rust oil for cold rolled steel strip.

[0055] The above process was used to prepare TiO 2 The test pieces were immersed in the TiO nanoparticles prepared in Examples 1-10. 2 After the test piece was taken out from the nanoparticle cold-rolled strip anti-rust oil, the anti-rust performance test was carried out according to SHT 0533 "Rust Assessment Method for Anti-Rust Grease Anti-Rust Test Specimen". Table 2 shows the implementation technical effects of the products obtained in Examples 1-10.

[0056] Table 2 Implementation effect of embodiments 1-10

[0057]

[0058] For any technician familiar with the art, without departing from the scope of the technical solution of the present invention, the technical content disclosed above can be used to make many possible changes and modifications to the technical solution of the present invention, or modified into equivalent embodiments with equivalent changes. Therefore, any simple modification, equivalent change and modification made to the above embodiments according to the technical essence of the present invention without departing from the content of the technical solution of the present invention should still fall within the scope of protection of the technical solution of the present invention.

Claims

1. A cold-rolled steel strip antirust oil containing TiO2 nanoparticles, characterized in that: The cold-rolled strip steel antirust oil comprises the following components in parts by mass: 3 to 10 parts of TiO2 nanoparticles, 2 to 10 parts of a composite surface modifier, 70 to 90 parts of a composite base oil, 5 to 15 parts of a composite rust inhibitor, 0.5 to 3 parts of a composite extreme pressure antiwear agent, 1 to 5 parts of a composite oiliness agent, 1 to 5 parts of a composite antioxidant, and 0.5 to 3 parts of a composite defoaming agent.

2. The cold-rolled strip antirust oil according to claim 1, characterized in that: The particle size of the TiO2 nanoparticles is in the range of 30 to 50 nm.

3. The cold-rolled strip antirust oil according to claim 1, characterized in that: The composite surface modifier is prepared by mixing a silane coupling agent, stearic acid and octadecenoic acid in a weight ratio of (2-3):2:

1.

4. The cold-rolled strip antirust oil according to claim 1, characterized in that: The composite base oil is prepared by mixing poly alpha-olefin PAO, dioctyl sebacate and triethyl phosphate in a weight ratio of (7-8):2:

1.

5. The cold-rolled strip antirust oil according to claim 1, characterized in that: The composite rust preventive is prepared by mixing petroleum barium sulfonate, aluminum stearate and zinc naphthenate in a weight ratio of (4-5):3:

2.

6. The cold-rolled strip antirust oil according to claim 1, characterized in that: The composite extreme pressure anti-wear agent is prepared by mixing sulfur chloride, sulfurized fatty acid ester and tricresyl phosphate in a weight ratio of 2: (2-3):

1.

7. The cold-rolled strip antirust oil according to claim 1, characterized in that: The composite oiliness agent is prepared by mixing stearic acid, butyl stearate and chlorinated paraffin in a weight ratio of 2: (2-3):

1.

8. The cold-rolled strip antirust oil according to claim 1, characterized in that: The composite antioxidant is prepared by mixing 2,6-di-tert-butyl-4-methylphenol and didodecanol thiodipropionate in a weight ratio of (1-2):

1.

9. The cold-rolled strip antirust oil according to claim 1, characterized in that: The composite defoamer is prepared by mixing silicone oil and polyether defoamer in a weight ratio of 1:(1-2).

10. A method for preparing the cold-rolled steel strip antirust oil containing TiO2 nanoparticles as claimed in claim 1, characterized in that: The preparation method comprises the following steps: ① Surface modification of TiO2 nanoparticles: mixing TiO2 nanoparticles with the prepared composite surface modifier, stirring and reacting at a temperature of 80°C to 95°C at a speed of 800 to 1000 rpm for 120 to 150 minutes; filtering the surface-modified TiO2 nanoparticles, and then drying at 90°C to 120°C to constant weight to obtain surface-modified TiO2 nanoparticles; ② Preheating the composite base oil: heat the composite base oil to 70°C to 85°C, stir at 800 to 1000 rpm, add the surface-modified TiO2 nanoparticles obtained in step ①, and stir for 30 to 45 minutes; ③ Add the composite rust inhibitor, stir at a speed of 900 to 1100 rpm, and stir for 15 to 20 minutes; ④ Add the composite extreme pressure anti-wear agent, stir at a speed of 1300-1500 rpm, and stir for 15-20 minutes; ⑤ Add the composite oiliness agent, stir at a speed of 1500-1700 rpm, and stir for 15-25 minutes; ⑥ Add the composite antioxidant, stirring at a speed of 1600-1800 rpm, and stir for 20-30 minutes; ⑦ Add the composite defoamer, stir at a speed of 1800-2000 rpm, and stir for 30-45 minutes; ⑧ After all the above components are added, stir at a stirring speed of 1800-2000 rpm for 120-150 minutes until the temperature of the anti-rust oil drops to room temperature, thereby obtaining a cold-rolled strip anti-rust oil containing TiO2 nanoparticles.

Citation Information

Patent Citations

  • Method for producing anticorrosive oil composition

    CN101503644A

  • Anti-rust oil for machine part packing

    CN105296103A

  • Electrostatic spraying antirust oil for cold-roll steel sheets and preparation and performance testing method thereof

    CN110283641A

  • Anti-wear lubricating oil additive for mechanical equipment and preparation method thereof

    CN110484328A

  • Lubricating oil and preparation method thereof

    CN112795419A

Cited By

  • Titanium steel cold rolling oil as well as preparation method and application thereof

    CN122278537A